2012
DOI: 10.1002/tox.21801
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanol‐induced cell death (necrosis) in human lung cancer A549 cells is mediated through increasing reactive oxygen species and decreasing the level of mitochondrial membrane potential

Abstract: Chrysophanol (1,8-dihydroxy-3-methylanthraquinone) is one of the anthraquinone compounds, and it has been shown to induce cell death in different types of cancer cells. The effects of chrysophanol on human lung cancer cell death have not been well studied. The purpose of this study is to examine chrysophanol-induced cytotoxic effects and also to investigate such influences that involved apoptosis or necrosis in A549 human lung cancer cells in vitro. Our results indicated that chrysophanol decreased the viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…It has been shown to trigger necrosis of the liver cancer cells by inducing the formation of ROS [10][11][12][13]. Similarly, in A549 lung cancer cells, chrysophanol causes the reduction of MMP loss to trigger cell death [11]. In yet another study, chrysophanol halted the ATP synthesis in liver cancer cells [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to trigger necrosis of the liver cancer cells by inducing the formation of ROS [10][11][12][13]. Similarly, in A549 lung cancer cells, chrysophanol causes the reduction of MMP loss to trigger cell death [11]. In yet another study, chrysophanol halted the ATP synthesis in liver cancer cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chrysophanol inhibits the growth of cancer cells through different mechanisms [10]. It has been shown to trigger necrosis of the liver cancer cells by inducing the formation of ROS [10][11][12][13]. Similarly, in A549 lung cancer cells, chrysophanol causes the reduction of MMP loss to trigger cell death [11].…”
Section: Discussionmentioning
confidence: 99%
“…They are generated as by-products of electron transport through the mitochondrial respiratory chain as well as by γ-ray and ultraviolet light irradiations (Kaur et al, 2001). ROS are highly reactive toward intracellular macromolecules (DNA, proteins and lipids), causing severe lesions that can lead to the cell death by either necrosis or apoptosis, depending on the intensity of the oxidative stimuli (He et al, 2012;Ni et al, 2012;Plante et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, in China most cancer-related deaths are also due to lung cancer (Ni et al, 2014). In about 35-40% of patients, lung cancer advances to the metastatic stage with brain, bone and liver (Ferlay et al, 2010;Herbst et al, 2008).…”
Section: Introductionmentioning
confidence: 55%